Bargaining with Intertemporal Maximin Payoffs - Vincent Martinet; Pedro Gajardo; Michel De Lara (Center for Economic Studies and ifo Institute (CESifo), 2019)
We frame sustainability problems as bargaining problems among stakeholders who have to agree on a common development path. For infinite alternatives, the set of feasible payoffs is unknown, limiting the possibility to apply classical bargaining theory and mechanisms. We define a framework accounting for the economic environment, which specifies how the set of alternatives and payoff structure underlie the set of feasible payoffs and disagreement point. A mechanism satisfying the axioms of Independence of Non-Efficient Alternatives and Independence of Redundant Alternatives can be applied to a reduced set of alternatives producing all Pareto-efficient outcomes of the initial problem, and produces the same outcome. We exhibit monotonicity conditions under which such a subset of alternatives is computable. We apply our framework to dynamic sustainability problems. We characterize a “satisficing” decision rule achieving any Pareto-efficient outcome. This rule is renegotiation-proof and generates a time-consistent path under the axiom of Individual Rationality.
Keywords: 330; social choice; axiomatic bargaining theory; economic environment; monotonicity; dynamics; sustainability; intergenerational equity; maximin